Expression of Genes Encoding the Enzymes for Glycogen and Trehalose Metabolism in L3 and L4 Larvae of Anisakis simplex - E. Łopieńska-Biernat; E. A. Zaobidna; M. Dmitryjuk (Journal of Parasitology Research)
Trehalose and glycogen metabolism plays an important role in supporting life processes in many nematodes, including Anisakis simplex. Nematodes, cosmopolitan helminths parasitizing sea mammals and humans, cause a disease known as anisakiasis. The aim of this study was to investigate the expression of genes encoding the enzymes involved in the metabolism of trehalose and glycogen—trehalose-6-phosphate synthase (TPS), trehalose-6-phosphate phosphatase (TPP), glycogen synthase (GS), and glycogen phosphorylase (GP)—in stage L3 and stage L4 larvae of A. simplex. The expression of mRNA all four genes, tps, tpp, gs, and gp, was examined by real-time polymerase chain reaction. The A. simplex ribosomal gene (18S) was used as a reference gene. Enzymatic activity was determined. The expression of trehalose enzyme genes was higher in L3 than in L4 larvae, but an inverse relationship was noted for the expression of gs and gp genes.